Analysis of The Implementation of Character Education at Madrasah Tsanawiyah Muhammadiyah Gedongtengen Yogyakarta - Permadi, Bagus Damar Galih; Achadi, Muh. Wasith (FKIP - Universitas Riau, 2025)
This study aims to analyze the management of the implementation of character education at MTs Muhammadiyah Gedongtengen Yogyakarta. This program is motivated by institutional anxiety about the negative impact of social media, such as the rise of extreme thinking, and the need to fortify students' character in line with the vision of the madrasah. This study uses a qualitative approach with a case study design. Primary data were collected through semi-structured in-depth interviews with Madrasah Heads, Vice Heads, and PAI teachers, and validated through observation and documentation. The results of the study show that implementation runs as a holistic management cycle. Planning is participatory by involving cross-disciplinary teachers. The implementation of a unique service culture pressure, namely